The Co-Constitution of Health Systems and Innovation; Comment on "What Health System Challenges Should Responsible Innovation in Health Address? Insights From an International Scoping Review" - Alexander Peine (Kerman University of Medical Sciences, 2019)
Lehoux et al provide a timely and relevant turn on the broad and ongoing discussion around the introduction of health technology and innovation. More specifically, the authors suggest a demand-driven approach to health innovation that starts from identifying challenges and demands at the health system level. In this commentary, I review a number of underlying implications of their study in relation to positions of technology push and techno-optimism, and to the narrow focus on health technology assessment on economic and clinical values. While Lehoux et al's scoping review provides very relevant insights with the potential to drive further empirical research, it is less clear about its conceptual basis. In particular, the somewhat artificial distinction between health innovations and health systems is worth further scrutiny. I discuss some potential risks of this separation, and propose to more openly address the co-constitution of health, health systems and technology in future research along the lines suggested by Lehoux et al.